2013
DOI: 10.1021/co400086u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Substituted 4H-Pyrido[1,2-a]pyrimidines via a One-Pot Three-Component Condensation Reaction

Abstract: A one-pot three-component reaction, involving condensation of 2-aminopyridines, aldehydes, and ketones/aldehydes under trifluoromethanesulfonic acid catalysis, provides rapid access to highly substituted novel 4H-pyrido[1,2-a]pyrimidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Dihydropyrimidinone derivatives 355 have been synthesized from the reaction of ethyl acetoacetate derivatives 352, aldehydes, and thiourea/urea (353, 354) through a Biginelli-type reaction in the presence of acid functionalized ionic liquid derived from Scheme 105 One-pot synthesis of dihydrotetrazolo [1,5-a] . A broad range of aromatic and aliphatic ketones and aldehydes were introduced in this study to know the generality of the reaction and the results were found in good agreement [214].…”
Section: Synthesis Of Pyrimidinesmentioning
confidence: 70%
“…Dihydropyrimidinone derivatives 355 have been synthesized from the reaction of ethyl acetoacetate derivatives 352, aldehydes, and thiourea/urea (353, 354) through a Biginelli-type reaction in the presence of acid functionalized ionic liquid derived from Scheme 105 One-pot synthesis of dihydrotetrazolo [1,5-a] . A broad range of aromatic and aliphatic ketones and aldehydes were introduced in this study to know the generality of the reaction and the results were found in good agreement [214].…”
Section: Synthesis Of Pyrimidinesmentioning
confidence: 70%
“…Recently, synthesis of 4 H ‐pyrido[1,2‐ a ]pyrimidines using trifluoromethanesulfonic was reported . In this reaction, condensation of 2‐aminopyridines 20 , aldehydes 21 , and ketones or aldehydes 22 in the presence of trifluoromethanesulfonic acid as catalyst was carried out to prepare 4 H ‐pyrido[1,2‐ a ]pyrimidines 23 (Scheme ).…”
Section: The Mcrs Synthesis Of Pyridopyrimidinesmentioning
confidence: 99%
“…Pyrido[1,2‐α]pyrimidines are one important class of aza‐bridgehead fused heterocyclic scaffolds that demonstrates a broad range of biological and pharmacological activities such as anticancer, anxiolytic, antioxidant, anticonvulsant, antidepressant and antibacterial activities [26–31] . Recently, we have synthesized a novel pyrido[1,2‐α]pyrimidine derivative, 4‐imino‐4 H ‐pyrido[1,2‐α]pyrimidine‐3‐carbonitrile, and demonstrated its potent PL and ECL for the first time [32] .…”
Section: Introductionmentioning
confidence: 99%